Local Allometric Equations for Estimating Above-Ground Biomass (AGB) of Mangroves (Rhizophora spp. and Avicennia germinans) from the Komo, Mondah and Rio Mouni Estuaries in Gabon - Igor Akendengue Aken; Okanga-Guay Marjolaine; Ondo Assoumou Emmanuel; Ajonina Gordon Nwutih; Mombo Jean-Bernard (European Scientific Journal, ESJ, 2021)
The aboveground biomass (AGB) of Gabonese mangroves is commonly estimated from equations calibrated in other countries, and is generally adapted poorly to the local context. This paper focuses on developing local allometric equations for the AGB estimation and to evaluate their accuracy compared to other general equations. The local equations for Rhizophora spp and Avicennia germinans were performed with tree volume, bark and wood densities, and are used with the diameter as an independent variable. The heights and diameters of 408 trees (314 Rhizophora spp and 94 Avicennia germinans) were measured at 13 sites in Estuaire Province. Sixty-four aliquots were taken from the trunks of both species at the Mondah site. This site has tree diameters ranging from 2 to 127 cm for Avicennia and from 1.4 to 75.8 cm for Rhizophora. The tree height ranges from 0.9 to 24 m for Avicennia, and from 1.1 to 53 m for Rhizophora. Avicennia has an overall trunk density of 0.88 g/cm3 and Rhizophora has 1.17 g/cm3. The coefficient of determination (R2) of the equations are 0.98 for Rhizophora spp, 0.97 for Avicennia germinans, and 0.99 for the general equation. The seven equation display biases that are less than 1% and the root mean square errors vary between 0.073 and 1.68. Compared to other equations generally used, these local equations improve the accuracy of aboveground biomass estimations of Gabonese mangroves.